The Smart Architecture of Smart Grid - Sen, A; Pal, S; Paul, R (International Journal of Computer Sciences and Engineering, 2020)
This paper state the analysis of change of structure of a power system by implementing modern grid network and also focus of modern structure of advanced power system for fulfilment of demands Energy is the basic necessity for the economic development of our country, many functions necessary to present day living grind to halt when the supply of energy stops. The main challenge today is to upgrade the existing technologies and to promote development, demonstration, scaling up and commercialisation of new and emerging technologies for widespread adaptation. India is resourceful country so India will be able to achieve a smooth transition from fossil fuel economy to sustainable renewable –energy-based economy and brings “Energy for all” and “Energy for ever” era for equitable, environment friendly and sustainable development. With increasing efforts worldwide to de-carbonise energy supply, a wide variety of generating plant types is being connected to electrical distribution network. So, in this paper we will focus different sectors of distribution generation.